2004
DOI: 10.1038/sj.gt.3302399
|View full text |Cite
|
Sign up to set email alerts
|

Complement regulatory proteins are incorporated into lentiviral vectors and protect particles against complement inactivation

Abstract: Lentiviral vectors pseudotyped with G glycoprotein from vesicular stomatitis virus (VSV-G) and baculovirus gp64 are inactivated by human complement. The extent of vector inactivation in serum from individual donors was examined and results showed wide donor-dependent variation in complement sensitivity for VSV-G-pseudotyped lentivectors. Amphotropic envelope (Ampho)-pseudotyped vectors were generally resistant to serum from all donors, while gp64-pseudotyped vectors were inactivated but showed less donor-to-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
1
33
1
Order By: Relevance
“…Furthermore, among the pseudotyped lentiviruses produced through an incorporation of each CRP, DAF-containing lentiviruses generated in the viral producer cells overexpressing a native form of DAF exhibited potent resistance to inactivation by human complement (33). However, our data indicated that pseudotype and recombinant VSVs bearing the GP64 produced in naive mammalian cells actively incorporate sufficiently large amounts of human DAF into viral particles to confer the particles with resistance to serum inactivation.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, among the pseudotyped lentiviruses produced through an incorporation of each CRP, DAF-containing lentiviruses generated in the viral producer cells overexpressing a native form of DAF exhibited potent resistance to inactivation by human complement (33). However, our data indicated that pseudotype and recombinant VSVs bearing the GP64 produced in naive mammalian cells actively incorporate sufficiently large amounts of human DAF into viral particles to confer the particles with resistance to serum inactivation.…”
Section: Discussioncontrasting
confidence: 50%
“…Lentiviral vectors pseudotyped with the baculovirus GP64 were found to be inactivated by human complement [Schauber, 2004]. In animal sera, the vectors were mostly resistant to inactivation by rodent complement, whereas canine complement caused a moderate reduction in titer [Schauber-Plewa, 2005]. Human complement-resistant pseudotyped HIV-1 vector particles were subsequently produced through incorporation of complement regulatory proteins.…”
Section: Lentiviral Vector Pseudotypes Containing the Baculovirus Gp6mentioning
confidence: 99%
“…The ability of viruses to activate complement as well as counteract complement pathways can play important roles in viral pathogenesis (e.g., see references 10, 29, and 41). In addition, it is increasingly clear that a greater understanding of complement interactions with viruses will be needed for the design of more effective viral vaccines and therapeutic vectors (31,39). The overall goal of the work described here was to understand the mechanisms by which the negative-strand RNA viruses mumps virus (MuV) and vesicular stomatitis virus (VSV) limit complement-mediated neutralization.…”
mentioning
confidence: 99%